Symmetric-type dispersion maps in dispersion-managed optical link with mid-span spectral inversion - Jea-Pil Chung; Seong-Real Lee (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In long-haul optical communication systems consisting of single-mode fiber spans and fiber amplifiers, such as an erbium-doped fiber amplifier, signal distortion causes performance to deteriorate because of group velocity dispersion and fiber nonlinearity. A combination of dispersion management and optical phase conjugation is an effective technique of compensating for the distortion. In an optical link configured with this combination, the dispersion map mainly affects the compensation for the distorted optical signals. Improvements in system performance have been reported for various types of dispersion maps. In this study, a symmetric type of dispersion map with respect to the midway optical phase conjugator is proposed. The effect of the proposed dispersion maps on the compensation for the distorted 24 channel × 40 Gbps wavelength-division-multiplexed signals was assessed through numerical simulation. It was confirmed that antipodal-type dispersion maps are most appropriate for the compensation, as well as for the flexibility of the link configuration.